Preparasi Detergen Penyuci Najis Air Liur Anjing dengan Variasi Konsentrasi Surfaktan Metil Ester Sulfonat (MES) - Tati Mardiyah; Imelda Fajriati (Kaunia: Integration and Interconnection Islam and Science Journal, 2022)
The kaolin detergent preparation as an alternative a dog saliva cleanser has been carried out by varying the concentration of Methyl Ester Sulfonate (MES) surfactant. This study aims to obtain the best kaolin detergent composition based on the results of physicochemical testing. The manufacture of kaolin detergent in this study has three stages. The first step is the preparation and characterization of kaolin using X-Ray Diffraction (XRD). The second step is the manufacture of kaolin detergent with various concentrations of MES surfactant by 10%, 14%, and 18% (w/w). The third step is testing the physicochemical properties which include organoleptic, pH, foam stability, and surface tension. The results showed that kaolin used in the manufacture of detergents has the main mineral content in the form of kaolinite is shown at 2θ=12,24o (d=7,24 Å) and 2θ=24,78o (d=3,58 Å). Based on the results of physicochemical testing, kaolin detergent F3 (MES 18%) was chosen as the best kaolin detergent because it has a thick and homogeneous liquid form, soft texture, white color, has a coconut milk smell, pH 8,270, and surface tension of 0,010 Nm-1.